Is Low Education a Risk Factor for Undiagnosed Angina? - McKee, Michael M. (2012)
BACKGROUND: Early awareness, recognition, and treatment of angina can help prevent or delay an acute myocardial infarction and potentially delay death. A patient’s educational level may affect a physician’s diagnosis of angina and/or a patient’s symptom recognition. OBJECTIVE: To determine whether low education is a risk factor for undiagnosed angina. DESIGN: Cross-sectional observational study (National Health and Nutrition Examination Survey 2001–2008). PARTICIPANTS: Nationally representative sample of adults ≥40 years with angina based on: physician diagnosis; and/or presence of angina symptoms based on the Rose Questionnaire. MEASURES: Educational attainment (high school and less vs. >high school) was the independent variable of interest. Undiagnosed angina (angina symptoms in the absence of angina diagnosis) was the dependent variable. METHODS: We used logistic regression to control for age, sex, race/ethnicity, income, and health care visit in past year. RESULTS: Low education was associated with undiagnosed angina (OR 1.43; 95% CI 1.01–2.03). Other undiagnosed angina predictors included being female, Black, and no health care visit in the past year. CONCLUSIONS: Low education is associated with undiagnosed angina. These results underscore the need for providers to ask about angina symptoms and confirm patients’ understanding of their angina diagnosis among those with low education.